ANALYSIS OF THE IMPLEMENTATION OF OBLIGATIONS FOR WITHHOLDING, PAYMENT AND REPORTING INCOME TAX ARTICLE 23 FOR OUTSOURCING SERVICES AT PT TEKNOLOGI RISET GLOBAL INVESTAMA - Kayla Cahya Apriliandra; Intan Puspanita; Anistya Vinta Desi; Vierina Clyde (Management Science Research Journal, 2026)
This writing aims to determine the implementation of the obligation to withhold, deposit, and report income tax article 23 on outsourcing services at PT Teknologi Riset Global Investama and to determine whether it is in accordance with applicable provisions. This paper uses a descriptive method with data collection techniques in the form of observation and documentation. The object of the paper is PT Teknologi Riset Global Investama. Based on data obtained in the field during the observation process in 2024, especially in June, there was an error in the withholding process, namely an error in determining the Taxable Basis (DPP), resulting in overpayment of tax to the state and underpayment to vendors. Based on the overpayment, the PT Teknologi Riset Global Investama made transfers (PBK) to several tax periods and other types of taxes and for the periods of July to December as well as 2025 and 2026, the withholding has been carried out in accordance with applicable provisions. The deposit process in 2024 to 2026 has been carried out on time according to the specified deadline. In addition, there was a delay in the reporting process for the 2024 period for the June tax periods due to the transfer process and perioed for the July SPT corrections. For the August to December period and in 2025 and 2026, Article 23 income tax reporting was completed in accordance with applicable regulations